The metabolic regulator PGC‐1α links anti‐cancer cytotoxic chemotherapy to reactivation of hepatitis B virus. Issue 1 (22nd May 2012) - Mouler Rechtman, M.; Burdelova, E. O.; Bar‐Yishay, I.; Ben‐Yehoyada, M.; Fishman, S.; Halpern, Z.; Shlomai, A.
<x xml:space="preserve">Abstract</x> Summary. Patients with chronic hepatitis B virus (HBV) infection are at an increased risk for a severe and a potentially fatal viral reactivation following anti‐cancer therapy. The molecular mechanism for this induction of HBV expression is still unclear. Here, we show that treating hepatoma cell line expressing HBV with various anti‐cancer cytotoxic agents results in a significant up‐regulation of HBV expression. This HBV induction is at the transcriptional level and is time dependent. Interestingly, treating hepatoma cells with anti‐cancer cytotoxic agents results in a robust induction of peroxisome proliferator‐activated receptor‐gamma coactivator‐1α (PGC‐1α), a metabolic and energy regulator that is normally induced in the liver under starvation conditions and that has been previously shown to strongly coactivate HBV transcription. Most importantly, HBV up‐regulation following anti‐cancer therapy depends on PGC‐1α induction, because PGC‐1α knock‐down abolishes HBV induction. Finally, pretreatment of HBV‐expressing cells with the antioxidant agent N‐acetylcysteine attenuates the induction of both PGC‐1α and HBV in response to anti‐cancer treatment, suggesting that chemotherapy‐associated PGC‐1α induction is mediated by cellular oxidative stress that ultimately leads to HBV up‐regulation. We conclude that cytotoxic anti‐cancer chemotherapy has a direct and an immune system‐independent effect on HBV gene expression, which is mediated by PGC‐1α. Our results attribute to this metabolic regulator an unexpected role in linking anti‐cancer treatment to HBV reactivation and make PGC‐1α a potential target for future anti‐HBV therapy, especially under conditions in which it is robustly induced, such as following anti‐cancer treatment.